Inducción y contrastación en la teoría organizacional y el management (2019)
The purpose of this article is to question the played role for the induction and falsiﬁcation in the organizational theory and management discipline upholding the theory’s arguments done by Karl Popper, and connecting them with the process of the theory’s development since the administration’s point of view. It will analyze speciﬁcally the development of the Resource Dependence Theory by Pfeﬀ er and Salancik at the end of the 70’s decade, and the problem of management fads exposed by Huczynski in 1993, giving evidence of the importance of the induction and falsiﬁcation, through testing, in the construction of the administration’s theory. This article concludes what is happening about the theory’s development in the administration, and the possible present threats for the evolution and consolidation of the administration discipline.